Gene therapy for cystic fibrosis. - Davies,JC; Alton,EWFW (Proc Am Thorac Soc, 2010)
The report of the first patients with cystic fibrosis (CF) to receive cystic fibrosis transmembrane conductance regulator gene (CFTR) therapy appeared in 1993, and since then there have been more than 20 clinical trials of both viral and nonviral gene transfer agents. These have largely been single dose to either nose or lower airway and have been designed around molecular or bioelectrical outcome measures. Both transgene mRNA and partial correction of chloride secretion have been reported, although sodium hyperabsorption has not been improved. The U.K. Cystic Fibrosis Gene Therapy Consortium is focused on a clinical program to establish whether these proof-of-principle measures translate into clinical benefit. Here, we review the published literature, discuss the limitations to gene therapy in the CF airway, and consider issues influencing the design of clinical trial programs.